Code Switching Found in Eva Alicia’s Video on Her Tiktok - Nurchurifiani, Eva; Meisya, Adinda; Alfiawati, Riska; Wahyuningsih, Sri (LPPM STKIP PGRI Bandar Lampung, 2025)
Code-switching refers to the alternating use of two languages within an utterance in a given situation. This case study was conducted to identify the types and reasons for code-switching in Alicia Eva's TikTok videos. The researchers employed a descriptive qualitative research design. Data collection involved the use of documentation and transcription as research instruments. The process involved watching videos, transcribing the spoken content, and analyzing it using theoretical frameworks to classify the types and reasons for code-switching. All results were analyzed using Poplack's (1980) theory to determine the types of code-switching and Hoffman's (1991) theory to determine the reasons behind it. The findings revealed that intra-sentential code-switching had been the most frequently used type in Alicia Eva's videos, with